2018
DOI: 10.1002/jpen.1416
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Protein Supplementation in Critically Ill Children: A Randomized Controlled Pilot and Feasibility Study

Abstract: Background Loss of muscle mass in critically ill children can negatively impact outcomes. The aims of this study were to conduct a pilot randomized control trial (RCT) to examine the difference in protein delivery and nitrogen balance in critically ill children with enteral protein supplementation vs controls. We also aimed to assess the feasibility, safety, and tolerance of the pilot trial. Methods This is a 3‐arm RCT in critically ill children eligible for enteral nutrition (EN) therapy. Patients were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…There is preliminary evidence to suggest that increased delivery of target protein may reduce the risk of mortality. 2,[31][32][33] Based on our results, we identified a moderate effect size of 0.4 based on protein delivery from initial to first goal study feed. Differences in protein delivery may be a better effect size on which to design future studies.…”
Section: F I G U R E 4 Oxygenation Saturation Index Levels By Study D...mentioning
confidence: 86%
“…There is preliminary evidence to suggest that increased delivery of target protein may reduce the risk of mortality. 2,[31][32][33] Based on our results, we identified a moderate effect size of 0.4 based on protein delivery from initial to first goal study feed. Differences in protein delivery may be a better effect size on which to design future studies.…”
Section: F I G U R E 4 Oxygenation Saturation Index Levels By Study D...mentioning
confidence: 86%
“…(2012),13 which showed that 57 kcal/kg per day and 1.5 g/kg/day of protein were required to achieve positive protein balance, no effectiveness review has been conducted examining the impact of protein intake, and reporting energy intake, on clinical outcomes in critically ill children. Several randomized controlled trials, including recent ones, have assessed the impact of protein intake higher than 1.5 g/kg per day in critically ill children, and reporting energy intake 19–25. Conducting this review will improve our understanding of the impact of high vs lower protein intake on clinical outcomes, considering energy intake, in critically ill children.…”
Section: Introductionmentioning
confidence: 99%
“…Several randomized controlled trials, including recent ones, have assessed the impact of protein intake higher than 1.5 g/kg per day in critically ill children, and reporting energy intake. [19][20][21][22][23][24][25] Conducting this review will improve our understanding of the impact of high vs lower protein intake on clinical outcomes, considering energy intake, in critically ill children. It may also clarify this impact on different age groups, including newborns, infants, children, and adolescents, where possible.…”
Section: Introductionmentioning
confidence: 99%